Penyuluhan Gizi Seimbang Pada Anak Dan Remaja Di Panti Asuhan Qurrotu’ Ayun Batam Center, Kota Batam - Justiyulfah Syah; Desy Desy; Roza Erda; Nurul Oktavia Asyriani (Pusat Riset dan Inovasi Nasional, 2022)
Indonesia is currently facing various health and nutrition problems. Indonesia experiences a triple burden of nutritional problems, namely malnutrition, excess nutrition (obesity) and micronutrient deficiencies. To overcome this nutritional problem, it can be done by implementing balanced nutrition. Balanced nutrition is a daily food composition that contains nutrients in types and quantities that suit the body's needs, taking into account the principles of food diversity or variety, physical activity, cleanliness and ideal body weight.Objective: Service activities are carried out to increase knowledge about balanced nutrition, determine nutritional status, and as a training tool for nutrition students in providing nutrition and health education to the community. This activity is expected to increase knowledge of balanced nutrition for children and adolescents at the Qurrotu A'yun Batam Center Orphanage.Conclusion: This counseling activity was carried out at the Qurrotu A'yun Batam Center Orphanage, Batam City, which was attended by children and teenagers. The activity consisted of an opening led by a team of lecturers and continued by reading material presented by a team of lecturers and students. Then the moderator returned to the event for a question and answer session and continued with measuring nutritional status and providing snacks to posyandu participants.